Rhus Verniciflua Stokes Inhibits PD-1 Expression and Induces Anticancer Effects by Enhancing T Cell Function - Seoyoung Kim PhD; Young-Kwan Lee PhD; Wang-Jun Lee MD, PhD; Hyoun Jong Moon MD, PhD; Sanghun Lee KMD, PhD (Integrative Cancer Therapies)
Background: Over the last decade, the anticancer effects of Rhus verniciflua Stokes (RVS) have been reported in various preclinical or clinical studies. However, the effects of RVS on immuno-oncology, especially on the functional properties of T cells and their phenotypes, remain unclear. Here, we planned to investigate the impact of RVS on immuno-oncology, specifically focusing on its effects on T cells. Methods Peripheral blood mononuclear cells (PBMCs) from breast cancer patients were isolated to obtain cytokine-induced killer cell populations with >85% CD3+ T cells. The anticancer activity of these T cells was evaluated by introducing red fluorescent protein (RFP) into HLA-A02:01 type-matched breast cancer cell lines (MCF7 and MDA-MB-231) and analyzing the results using flow cytometry. The effect of RVS extracts on T cell phenotype was assessed using markers such as CTLA-4 and PD-1, as well as mRNA expression levels of key genes (IFN-γ, TNF-α, and IL-2). Results RVS treatment significantly enhanced the anticancer activity of T cells against breast cancer cells. Specifically, T cells treated with 100 µg/mL of RVS showed a 20.6% increase in cytotoxicity against MCF-7 cells and a 36.2% increase against MDA-MB231 cells compared to the control. Additionally, RVS treatment led to a significant reduction in PD-1 expression on T cells. Conclusion: Our findings demonstrate that RVS treatment enhances T cell function against breast cancer cells by reducing PD-1 expression. These results suggest that components of RVS may serve as potential candidates for restoring exhausted T cells in cancer therapy.